A lithium ion battery
By using specific additives in non-aqueous electrolytes in lithium-ion batteries and controlling the particle distribution of negative electrode materials, the problem of reducing liquid-solid transformation and lithium-ion transmission efficiency of lithium-ion batteries under low temperature conditions is solved, and high temperatures are achieved and excellent battery performance under low temperature conditions.
Patent Information
- Application Number
- CN202411415582.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-11
AI Technical Summary
Existing lithium-ion batteries are difficult to take into account both high-temperature and low-temperature performance, especially the liquid-solid transformation of electrolyte and the reduction in lithium-ion transmission efficiency under low temperature conditions lead to attenuation of battery performance.
A lithium-ion battery is adopted, which includes a positive electrode, an anode and a nonaqueous electrolyte. The negative electrode material layer contains a negative electrode material. Vityl carbonate, lithium difluorophosphate and vinyl sulfate are added as additives to the nonaqueous electrolyte and control it. The ratio of D50/D90 of the negative electrode material and the ratio of additives in the non-aqueous electrolyte meets specific conditions to optimize the film formation quality of the negative electrode surface interface film.
The electrochemical performance of lithium-ion batteries that avoid the decomposition of nonaqueous electrolytes under high temperature conditions and maintain low impedance under low temperature conditions, taking into account the battery performance at high and low temperatures.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy storage components, and in particular relates to a lithium ion battery. Background Art
[0002] Lithium-ion batteries have become the first choice for the automotive industry to produce pure electric vehicles (EVs) due to their high energy density, low self-discharge, long life, environmental protection, and reasonable cost. However, due to the increase in electrolyte viscosity and the decrease in lithium ion transmission efficiency at low temperatures, how to ensure the high-temperature performance of electric vehicles while taking into account the performance at low temperatures is a problem that needs to be solved.
[0003] Under low temperature conditions, slow reaction kinetics and liquid-solid transition of electrolyte are the main failure manifestations of lithium-ion batteries. Problems such as decreased electrolyte conductivity, increased desolvation energy of solvated lithium ions at the electrode / electrolyte interface, and decreased diffusion rate of lithium ions in electrode materials will lead to attenuation of battery performance, such as loss of battery capacity. In addition, slow reaction kinetics will also lead to severe polarization of electrochemical reactions, that is, lithium ions are easily deposited on the surface of negative electrode materials to form metallic lithium, promote the formation of lithium dendrites, and easily induce safety problems such as battery short circuit. Under high temperature conditions, severe side reactions and interface instability will accelerate the degradation of lithium-ion batteries. Among them, the dissolution of transition metal ions in the positive electrode material caused by hydrofluoric acid produced by thermal decomposition of the electrolyte is particularly serious. At the same time, high temperature conditions will also increase the risk of thermal runaway of the battery and cause battery safety issues.
[0004] For electrolytes, temperature has a significant impact on their own properties and the properties related to the electrode interface. When the temperature exceeds the normal operating temperature range of the electrolyte, the electrolyte will undergo irreversible chemical reactions (such as high-temperature oxidation decomposition) or physical changes (such as solidification in a low-temperature environment causing a sudden drop in conductivity), causing the battery performance to fail rapidly, and even leading to safety accidents. Existing battery designs often increase the lower operating temperature limit while increasing the upper operating temperature limit, or decrease the upper operating temperature limit while reducing the lower operating temperature limit, making it difficult to obtain lithium-ion batteries that take into account both high and low temperatures. Summary of the invention
[0005] In view of the problem that existing lithium ion batteries are difficult to achieve both high temperature performance and low temperature performance, the present invention provides a lithium ion battery.
[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0007] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the negative electrode comprises a negative electrode material layer containing a negative electrode material, the non-aqueous electrolyte comprises a non-aqueous organic solvent, a lithium salt and an additive, and the additive comprises vinylene carbonate, lithium difluorophosphate and vinyl sulfate;
[0008] The lithium-ion battery meets the following conditions:
[0009] 0.08≤D×A / X≤8, and 0.25≤D≤0.9, 0.1≤X≤2.5, 0.3≤A≤2;
[0010] Where D is the D50 / D90 ratio of the negative electrode material;
[0011] X is the mass content ratio of vinylene carbonate to lithium difluorophosphate in the non-aqueous electrolyte;
[0012] A is the sum of the mass fractions of vinylene carbonate, vinyl sulfate and lithium difluorophosphate in the non-aqueous electrolyte, expressed in wt%.
[0013] Optionally, the lithium-ion battery meets the following conditions:
[0014] 0.2≤D×A / X≤7.
[0015] Optionally, the D50 / D90 ratio D of the negative electrode material is 0.3-0.75; and / or
[0016] The D50 of the negative electrode material is 9-20 μm; and / or
[0017] The D90 of the negative electrode material is 18-45 μm.
[0018] Preferably, the D50 of the negative electrode material is 10-16 μm; and / or
[0019] The D90 of the negative electrode material is 20-40 μm.
[0020] Optionally, the mass content ratio X of vinylene carbonate to lithium difluorophosphate in the non-aqueous electrolyte is 0.15-1; and / or
[0021] The mass percentage of vinylene carbonate in the non-aqueous electrolyte is 0.05% to 0.5%; and / or
[0022] The mass percentage of lithium difluorophosphate in the non-aqueous electrolyte is 0.1% to 1%;
[0023] Preferably, the mass percentage of vinylene carbonate in the non-aqueous electrolyte is 0.1% to 0.35%; and / or
[0024] The mass percentage of lithium difluorophosphate in the non-aqueous electrolyte is 0.3% to 0.75%.
[0025] Optionally, the total mass fraction A of vinylene carbonate, vinyl sulfate and lithium difluorophosphate in the non-aqueous electrolyte is 0.6% to 1.6%; and / or
[0026] The mass percentage of vinylene carbonate in the non-aqueous electrolyte is 0.05% to 0.5%; and / or
[0027] The mass percentage of lithium difluorophosphate in the non-aqueous electrolyte is 0.1% to 1%; and / or
[0028] The mass percentage of vinyl sulfate in the non-aqueous electrolyte is 0.01% to 1%;
[0029] Preferably, the mass percentage of vinylene carbonate in the non-aqueous electrolyte is 0.1% to 0.35%; and / or
[0030] The mass percentage of lithium difluorophosphate in the non-aqueous electrolyte is 0.3% to 0.75%; and / or
[0031] The mass percentage of vinyl sulfate in the non-aqueous electrolyte is 0.05% to 0.75%.
[0032] Optionally, in the non-aqueous electrolyte, the mass percentage of lithium difluorophosphate is greater than the mass percentage of vinyl sulfate.
[0033] Optionally, the non-aqueous organic solvent comprises ethylene carbonate and ethyl methyl carbonate, the mass content ratio of ethylene carbonate to ethyl methyl carbonate in the non-aqueous organic solvent is 0.15-0.6, and the mass percentage of ethyl methyl carbonate in the non-aqueous organic solvent is greater than or equal to 20%, and / or
[0034] The non-aqueous organic solvent does not contain carboxylic acid ester.
[0035] Optionally, the negative electrode active material includes one or more of artificial graphite and natural graphite.
[0036] Optionally, the positive electrode includes a positive electrode material layer containing a positive electrode active material, and the positive electrode active material includes a compound represented by formula (A):
[0037] Li 1+x Ni a Co b M' 1-a-b O 2-y A y Formula (A)
[0038] In formula (A), -0.1 ≤ x ≤ 0.2, 0.5 < a < 1, 0 ≤ b < 0.3, 0.6 < a + b < 1, 0 ≤ y < 0.2, M' includes Mn, and includes zero, one, or more of B, Ga, F, W, Zr, Mg, Na, Pb, K, Al, Cr, Ba, Ca, Ni, Sr, Ti, Zn, Si, V, Mo, Nb, and A includes one or more of S, N, F, B, Cl, Br, and I.
[0039] Optionally, the additive further includes at least one of cyclic sulfate compounds, sultone compounds, cyclic carbonate compounds, phosphate compounds, and nitrile compounds;
[0040] The cyclic sulfate compounds include at least one of propylene sulfate and vinyl methyl sulfate; and / or
[0041] The sultone compounds include at least one of 1,3-propane sultone, 1,4-butane sultone, and 1,3-propene sultone; and / or
[0042] The cyclic carbonate compounds include at least one of ethylene carbonate, vinylene carbonate, fluoroethylene carbonate, or the compound shown in Structural Formula 1:
[0043]
[0044] In Structural Formula 1, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 are each independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group; and / or
[0045] The phosphate compounds include at least one of tris(trimethylsilyl) phosphate, tris(triethylsilyl) phosphate, or the compound shown in Structural Formula 2:
[0046]
[0047] In Structural Formula 2, R 31 , R 32 , R 33 are each independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, and a C1-C5 halogenated hydrocarbon group, and at least one of R 31 , R 32 , R 33 is an unsaturated hydrocarbon group; and / or
[0048] The nitrile compound includes at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.
[0049] According to the lithium ion battery provided by the present invention, vinylene carbonate, lithium difluorophosphate and vinyl sulfate are added to the non-aqueous electrolyte as additives. Vinylene carbonate, lithium difluorophosphate and vinyl sulfate will decompose on the surface of the negative electrode active material during the battery formation stage, and the decomposition products of the three together form a negative electrode surface interface film. The negative electrode surface interface film has a certain protective effect on the negative electrode active material, which is beneficial to avoid the decomposition side reaction of the non-aqueous electrolyte on the surface of the negative electrode active material at high temperature, and at the same time allows the negative electrode active material and the non-aqueous electrolyte to exchange ions. However, the inventors have found that when negative electrode active materials with different particle specifications are used, the film quality of the negative electrode surface interface film is not completely consistent, which is mainly reflected in the difference in film density and ion conductivity. When the film density is higher, the high temperature performance of the lithium ion battery is better, but it will affect the exchange efficiency of lithium ions, resulting in an increase in the impedance of the lithium ion battery at low temperatures and a decrease in the battery capacity. Therefore, the inventors have further found that when the negative electrode material When the D50 / D90 ratio D, the mass content ratio X of vinylene carbonate to lithium difluorophosphate, and the sum of the mass fractions A of vinylene carbonate, vinyl sulfate and lithium difluorophosphate meet the conditions of 0.15≤D×A / X≤8, and 0.25≤D≤0.9, 0.1≤X≤2.5, and 0.3≤A≤2, the obtained lithium ion battery exhibits excellent performance under both high temperature and low temperature conditions. It is speculated that by controlling the D50 / D90 ratio of the negative electrode material, different surface morphologies and particle overlapping effects are formed, thereby affecting the film formation uniformity of the negative electrode surface interface film. At the same time, by regulating the relative proportions of vinylene carbonate, vinyl sulfate and lithium difluorophosphate, the purpose of regulating the composition of the negative electrode surface interface film is achieved. When the D value, X value and A value reach the synergistic condition, a negative electrode surface interface film that is both dense and has good ion conductivity can be obtained, thereby ensuring that the lithium ion battery avoids the decomposition of the non-aqueous electrolyte under high temperature conditions and has low impedance electrochemical performance under low temperature conditions. DETAILED DESCRIPTION
[0050] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0051] In the description of the present invention, the term "D50" refers to the median particle size of the negative electrode material in the negative electrode material layer, indicating that 50% of the particle sizes in the negative electrode material layer are less than or equal to this value. The term "D90" means that 90% of the particle sizes in the negative electrode material layer are less than or equal to this value.
[0052] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the negative electrode comprises a negative electrode material layer containing a negative electrode material, the non-aqueous electrolyte comprises a non-aqueous organic solvent, a lithium salt and an additive, and the additive comprises vinylene carbonate, lithium difluorophosphate and vinyl sulfate;
[0053] The lithium-ion battery meets the following conditions:
[0054] 0.08≤D×A / X≤8, and 0.25≤D≤0.9, 0.1≤X≤2.5, 0.3≤A≤2;
[0055] Where D is the D50 / D90 ratio of the negative electrode material;
[0056] X is the mass content ratio of vinylene carbonate to lithium difluorophosphate in the non-aqueous electrolyte;
[0057] A is the sum of the mass fractions of vinylene carbonate, vinyl sulfate and lithium difluorophosphate in the non-aqueous electrolyte, expressed in wt%.
[0058] Vinyl carbonate (VC), lithium difluorophosphate (LiPO2F2) and vinyl sulfate (DTD) are added to the non-aqueous electrolyte as additives. Vinyl carbonate, lithium difluorophosphate and vinyl sulfate will decompose on the surface of the negative electrode active material during the battery formation stage. The decomposition products of the three together form a negative electrode surface interface film. The negative electrode surface interface film has a certain protective effect on the negative electrode active material, which is beneficial to avoid the decomposition side reaction of the non-aqueous electrolyte on the surface of the negative electrode active material at high temperature, and at the same time allows the negative electrode active material and the non-aqueous electrolyte to exchange ions. However, the inventors have found that when negative electrode active materials with different particle specifications are used, the film quality of the negative electrode surface interface film is not completely consistent, which is mainly reflected in the difference in film density and ion conductivity. When the film density is higher, the high temperature performance of the lithium ion battery is better, but it will affect the exchange efficiency of lithium ions, resulting in an increase in the impedance of the lithium ion battery at low temperatures and a decrease in the battery capacity. Therefore, the inventors have further found that when the negative electrode When the D50 / D90 ratio D of the material, the mass content ratio X of vinylene carbonate to lithium difluorophosphate, and the sum of the mass fractions A of vinylene carbonate, vinyl sulfate and lithium difluorophosphate meet the conditions of 0.08≤D×A / X≤8, and 0.25≤D≤0.9, 0.1≤X≤2.5, and 0.3≤A≤2, the obtained lithium ion battery exhibits excellent performance under both high temperature and low temperature conditions. It is speculated that by controlling the D50 / D90 ratio of the negative electrode material, different surface morphologies and particle overlapping effects are formed, thereby affecting the film formation uniformity of the negative electrode surface interface film. At the same time, by regulating the relative proportions of vinylene carbonate, vinyl sulfate and lithium difluorophosphate, the purpose of regulating the composition of the negative electrode surface interface film is achieved. When the D value, X value and A value reach the synergistic condition, a negative electrode surface interface film that is both dense and has good ion conductivity can be obtained, thereby ensuring that the lithium ion battery avoids the decomposition of the non-aqueous electrolyte under high temperature conditions and has low impedance electrochemical performance under low temperature conditions.
[0059] In a preferred embodiment, the lithium-ion battery meets the following conditions:
[0060] 0.2≤D×A / X≤7.
[0061] When the D50 / D90 ratio D of the negative electrode material, the mass content ratio X of vinylene carbonate to lithium difluorophosphate and the sum of the mass fractions A of vinylene carbonate, vinyl sulfate and lithium difluorophosphate further meet the above conditions, it is beneficial to further improve the capacity retention rate of the lithium-ion battery after high temperature storage and the capacity retention rate under low temperature conditions.
[0062] In a specific embodiment, the D50 / D90 ratio D of the negative electrode material can be 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.9 or a range between any two of the above values.
[0063] In a preferred embodiment, the D50 / D90 ratio D of the negative electrode material is 0.3-0.75.
[0064] In the present invention, the negative electrode material refers to all materials contained in the negative electrode material layer, including the negative electrode active material, the negative electrode conductor and the negative electrode binder. Since the negative electrode active material accounts for the majority of the negative electrode material layer, the D50 / D90 ratio of the negative electrode material actually mainly reflects the D50 / D90 ratio of the negative electrode active material.
[0065] The D50 / D90 ratio D of the negative electrode material is directly related to the particle size distribution of the negative electrode active material. The design of the negative electrode particle size distribution is helpful to improve the density and mechanical properties of the negative electrode plate, reduce the occurrence of pores and defects, and enhance the strength and toughness of the plate; the lithium ion transmission rate can be improved and optimized to a certain extent, and more importantly, it affects the decomposition and deposition of vinyl carbonate, vinyl sulfate and lithium difluorophosphate on the surface of the negative electrode active material, which has a great influence on the film formation uniformity and film formation component composition; when the D50 / D90 ratio D of the negative electrode material is too small, it means that the particle size distribution of the negative electrode active material is wide, and the particle size difference is huge. More additives are needed to generate the negative electrode surface interface film based on the gaps and defects of the plate to stabilize ion transmission, which easily leads to the problem of uneven film formation; when the D50 / D90 ratio D of the negative electrode material is too large, the gaps between the negative electrode particles are large, which is not conducive to the improvement of the energy density of the lithium ion battery, and is also not conducive to the improvement of the film formation quality of the negative electrode surface interface film.
[0066] In some embodiments, the D50 of the negative electrode material is 9-20 μm.
[0067] In a specific embodiment, D50 of the negative electrode material may be 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm or a range between any two of the above values.
[0068] In a preferred embodiment, the D50 of the negative electrode material is 10-16 μm.
[0069] In some embodiments, the D90 of the negative electrode material is 18-45 μm.
[0070] In a specific embodiment, D90 of the negative electrode material may be 18 μm, 19 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, 40 μm, 42 μm, 45 μm or a range between any two of the above values.
[0071] In a preferred embodiment, the D90 of the negative electrode material is 20-40 μm.
[0072] The test method for D50 and D90 of the negative electrode material of the present invention is as follows: disassemble the battery, soak and clean the negative electrode sheet with dimethyl carbonate, place it in a glove box for vacuum drying for 24 hours, use a small scraper to scrape the surface powder, about 2-3 g, place the powder in the sampling chamber of the laser particle size analyzer, and test it after it is fully dispersed by ultrasound (≥20 min, no significant sedimentation) and the shading rate is stable.
[0073] The negative electrode surface interface film includes an organic component and an inorganic component, wherein the organic component is formed by the decomposition of the vinylene carbonate and the vinyl sulfate, and the organic component can ensure the flexibility of the negative electrode surface interface film; the inorganic component is formed by the decomposition of the lithium difluorophosphate, and can optimize the ion transmission capacity of the negative electrode surface interface film, while providing rigidity to support the stability of the negative electrode surface interface film, and has a certain impedance optimization effect.
[0074] In a specific embodiment, the mass content ratio X of vinylene carbonate to lithium difluorophosphate in the non-aqueous electrolyte can be 0.1, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.3, 2.4, 2.5 or the range between any two of the above values.
[0075] In a preferred embodiment, the mass content ratio X of vinylene carbonate to lithium difluorophosphate in the non-aqueous electrolyte is 0.15-1.
[0076] Vinyl carbonate and lithium difluorophosphate can provide repair of organic components and inorganic components of the negative electrode surface interface film respectively in the later stage of charge and discharge. Therefore, it is necessary to ensure that the ratio of the two is equal to ensure the uniformity and effectiveness of subsequent film repair; when the mass content ratio X of vinyl carbonate to lithium difluorophosphate in the non-aqueous electrolyte is too low, the inorganic component in the negative electrode surface interface film formed is relatively high, and the impedance of the lithium-ion battery at low temperature is reduced, but the negative electrode surface interface film has the risk of decomposition at high temperature; when the mass content ratio X of vinyl carbonate to lithium difluorophosphate in the non-aqueous electrolyte is too high, the organic component in the negative electrode surface interface film formed is relatively high, which is beneficial to improve its high temperature stability, but its ion conductivity is reduced.
[0077] When the mass content ratio X of vinyl carbonate to lithium difluorophosphate in the non-aqueous electrolyte satisfies 0.15-1, that is, the mass content of lithium difluorophosphate in the non-aqueous electrolyte is greater than or equal to the mass content of vinyl carbonate, it is beneficial to increase the proportion of the inorganic phase in the interface film on the surface of the negative electrode, improve the mechanical strength and structural stability of the interface film, and ensure the structural stability of the interface film during high-rate charging.
[0078] In some embodiments, the mass percentage of vinylene carbonate in the non-aqueous electrolyte is 0.05% to 0.5%.
[0079] In a preferred embodiment, the mass percentage of vinylene carbonate in the non-aqueous electrolyte is 0.1% to 0.35%.
[0080] In a specific embodiment, the mass percentage of vinylene carbonate in the non-aqueous electrolyte can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35% or a range between any two of the above values.
[0081] In some embodiments, the mass percentage of lithium difluorophosphate in the non-aqueous electrolyte is 0.01%~1%.
[0082] In a preferred embodiment, the mass percentage of lithium difluorophosphate in the non-aqueous electrolyte is 0.3% to 0.75%.
[0083] In a specific embodiment, the mass percentage of lithium difluorophosphate in the non-aqueous electrolyte can be 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75% or a range between any two of the above values.
[0084] In a specific embodiment, the sum A of the mass fractions of vinylene carbonate, vinyl sulfate and lithium difluorophosphate in the non-aqueous electrolyte can be 0.3%, 0.4%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.8%, 2% or the range between any two of the above values.
[0085] In a preferred embodiment, the total mass fraction A of vinylene carbonate, vinyl sulfate and lithium difluorophosphate in the non-aqueous electrolyte is 0.6% to 1.6%.
[0086] Vinyl sulfate is consumed rapidly in the film-forming stage, and the S-containing group can form an interface film substrate based on the negative electrode active material to connect other interface film components in series; vinyl carbonate effectively inhibits the embedding of solvent molecules and the gas expansion of lithium batteries, and can improve the capacity and cycle life of the battery, but excessive addition will cause an increase in impedance. Lithium difluorophosphate, as a lithium salt additive, participates in the formation of inorganic components of the negative electrode surface interface film; when the sum of the mass fractions A of vinyl carbonate, vinyl sulfate and lithium difluorophosphate in the non-aqueous electrolyte is too low, it is difficult to form a continuous and complete negative electrode surface interface film on the surface of the negative electrode active material; when the sum of the mass fractions A of vinyl carbonate, vinyl sulfate and lithium difluorophosphate in the non-aqueous electrolyte is too high, it is easy to increase the thickness of the negative electrode surface interface film, resulting in an increase in impedance. At the same time, there are more residual additives in the non-aqueous electrolyte, which is easy to cause unnecessary side reactions.
[0087] In some embodiments, the mass percentage of vinylene carbonate in the non-aqueous electrolyte is 0.05% to 0.5%.
[0088] In a preferred embodiment, the mass percentage of vinylene carbonate in the non-aqueous electrolyte is 0.1% to 0.35%.
[0089] In a specific embodiment, the mass percentage of vinylene carbonate in the non-aqueous electrolyte can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35% or a range between any two of the above values.
[0090] In some embodiments, the mass percentage of lithium difluorophosphate in the non-aqueous electrolyte is 0.1%~1%.
[0091] In a preferred embodiment, the mass percentage of lithium difluorophosphate in the non-aqueous electrolyte is 0.3% to 0.75%.
[0092] In a specific embodiment, the mass percentage of lithium difluorophosphate in the non-aqueous electrolyte can be 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75% or a range between any two of the above values.
[0093] In some embodiments, the mass percentage of vinyl sulfate in the non-aqueous electrolyte is 0.01%~1%.
[0094] In a preferred embodiment, the mass percentage of vinyl sulfate in the non-aqueous electrolyte is 0.05% to 0.75%.
[0095] In a specific embodiment, the mass percentage of vinyl sulfate in the non-aqueous electrolyte can be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75% or a range between any two of the above values.
[0096] In some embodiments, in the non-aqueous electrolyte, the mass percentage of lithium difluorophosphate is greater than the mass percentage of vinyl sulfate.
[0097] When the mass percentage of lithium difluorophosphate is greater than the mass percentage of vinyl sulfate, the inorganic component composition in the negative electrode surface interface film formed is higher than the organic component, and the diversity of the organic component is ensured, which is beneficial to the construction of the bonding network and also beneficial to improving the interface stability and high-temperature cycle stability under high-rate charging conditions.
[0098] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass content of the non-aqueous organic solvent is 65% to 90%.
[0099] Specifically, based on the total mass of the non-aqueous electrolyte as 100%, the mass content of the non-aqueous organic solvent can be 65%, 68%, 71%, 74%, 76%, 78%, 79%, 80%, 81.5%, 82%, 84%, 85%, 86%, 87%, 89%, or 90%.
[0100] In some embodiments, the non-aqueous organic solvent includes ethylene carbonate and ethyl methyl carbonate, the mass content ratio of ethylene carbonate to ethyl methyl carbonate in the non-aqueous organic solvent is 0.15~0.6, and the mass percentage of ethyl methyl carbonate in the non-aqueous organic solvent is greater than or equal to 40%.
[0101] The solvation structure of non-aqueous electrolyte affects the intrinsic stability of non-aqueous electrolyte. The solvation interaction between ethylene carbonate and ethyl methyl carbonate can increase the Li+ (EC) x (EMC) y The energy difference between the complex orbitals inhibits electron transfer, making the system more resistant to reduction; at the same time, it weakens the Li + -Solvent interactions, Li + It is easier to desolvate and the system stability is improved. When the mass content ratio of ethylene carbonate to ethyl methyl carbonate is controlled within the above range, the synergistic effect of the two is the best, which can reduce the lithium deposition / stripping polarization voltage and extend the cycle life in a wide temperature range.
[0102] In some embodiments, the mass percentage of diethyl carbonate in the non-aqueous electrolyte is less than or equal to 5%.
[0103] In some embodiments, the non-aqueous organic solvent does not contain carboxylic acid esters. Carboxylic acid esters are often used in the design of low-temperature electrolyte formulations. They have high ionic conductivity and viscosity, which are beneficial to low-temperature performance. However, under high-temperature conditions, carboxylic acid esters undergo decarboxylation reactions to generate acidic substances. The generated byproducts corrode electrode materials, destroy the interface film on the negative electrode surface, hinder the normal deintercalation of lithium ions, and affect the cycle life. In the battery system provided by the present invention, based on the consideration of high and low temperature comprehensive performance, carboxylic acid ester substances are not applicable.
[0104] In some embodiments, the carboxylic acid ester includes one or more of ethyl propionate, propyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate, and ethyl trimethylacetate.
[0105] In some embodiments, the non-aqueous organic solvent further comprises at least one of an ether solvent, a nitrile solvent, and a sulfone solvent.
[0106] In some embodiments, the ether solvent includes a cyclic ether or a chain ether, preferably a chain ether with 3 to 10 carbon atoms and a cyclic ether with 3 to 6 carbon atoms. The cyclic ether may be, but not limited to, at least one of 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); the chain ether may be, but not limited to, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether. Since the chain ether has a high solvation ability with lithium ions and can improve ion dissociation, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane, which have low viscosity and can impart high ionic conductivity, are particularly preferred. The ether compound can be used alone or in any combination and ratio. The amount of the ether compound added is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the high-density lithium-ion battery of the present invention. The volume ratio of the non-aqueous solvent is usually 1% or more, preferably 2% or more, and more preferably 3% or more, and the volume ratio is usually 30% or less, preferably 25% or less, and more preferably 20% or less.
[0107] In some embodiments, the nitrile solvent may specifically be but is not limited to at least one of acetonitrile, glutaronitrile, and malononitrile.
[0108] In some embodiments, the sulfone solvent includes a cyclic sulfone and a chain sulfone. Preferably, in the case of a cyclic sulfone, it is usually a compound with 3 to 6 carbon atoms, preferably 3 to 5 carbon atoms, and in the case of a chain sulfone, it is usually a compound with 2 to 6 carbon atoms, preferably 2 to 5 carbon atoms. There is no special restriction on the amount of sulfone solvent added, and it is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention. Relative to the total amount of solvent of the non-aqueous electrolyte, the volume ratio is usually 0.3% or more, preferably 0.5% or more, and more preferably 1% or more. In addition, the volume ratio is usually 40% or less, preferably 35% or less, and more preferably 30% or less. In the case of using two or more sulfone solvents in combination, the total amount of sulfone solvents can be made to meet the above range. When the amount of sulfone solvent added is within the above range, a non-aqueous electrolyte with excellent high temperature storage stability tends to be obtained.
[0109] In some embodiments, the negative electrode active material includes one or more of artificial graphite and natural graphite.
[0110] In some embodiments, in the negative electrode active material, the total mass of artificial graphite and natural graphite accounts for 90% or more.
[0111] The negative electrode active material also includes at least one of a silicon-based negative electrode, a tin-based negative electrode, and a lithium negative electrode. Among them, the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium-silicon alloy, a lithium-sodium alloy, a lithium-potassium alloy, a lithium-aluminum alloy, a lithium-tin alloy, and a lithium-indium alloy.
[0112] In some embodiments, the silicon material is one or more of silicon nanoparticles, silicon nanowires, silicon nanotubes, silicon thin films, 3D porous silicon, and hollow porous silicon.
[0113] In some embodiments, the negative electrode further comprises a negative electrode current collector, and the negative electrode active material layer covers the surface of the negative electrode current collector. The negative electrode current collector comprises a metal material that can conduct electrons, preferably, the negative electrode current collector comprises at least one of Al, Ni, tin, copper, and stainless steel, and in a more preferred embodiment, the negative electrode current collector is selected from copper foil.
[0114] In some embodiments, the negative electrode active material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are blended to obtain the negative electrode active material layer.
[0115] The negative electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.
[0116] The negative electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0117] In some embodiments, the positive electrode includes a positive electrode material layer containing a positive electrode active material, and the positive electrode active material includes a compound represented by formula (A):
[0118] Li 1+x Ni a Co b M' 1-a-b O 2-y A y Formula (A)
[0119] In formula (A), -0.1 ≤ x ≤ 0.2, 0.5 < a < 1, 0 ≤ b < 0.3, 0.6 < a + b < 1, 0 ≤ y < 0.2, M' includes Mn, and includes zero, one, or more of B, Ga, F, W, Zr, Mg, Na, Pb, K, Al, Cr, Ba, Ca, Ni, Sr, Ti, Zn, Si, V, Mo, Nb, and A includes one or more of S, N, F, B, Cl, Br, and I.
[0120] Specifically, in some embodiments of the present invention, the positive electrode active material includes LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.6 Co 0.1 Mn 0.3 O2, LiNi 0.7 Co 0.1 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.8 Co 0.15 Mn 0.05 O2, LiNi 0.85 Co 0.05 Mn 0.15 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.92 Co 0.05 Mn 0.03 O2, LiNi 0.95 Co 0.02 Mn 0.03 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.9 Co 0.05 Al 0.05 O2. The element E doped or coated in the positive electrode active material is selected from one or more of Fe, Zr, Mg, Ba, Ca, Cu, Zn, Ga, Nb, or Ti.
[0121] In some embodiments, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductive agent, and the positive electrode active material, the positive electrode binder, and the positive electrode conductive agent are blended to obtain the positive electrode material layer.
[0122] The positive electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.
[0123] The positive electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0124] In some embodiments, the positive electrode also includes a positive electrode current collector, the positive electrode material layer covers the surface of the positive electrode current collector, and the positive electrode current collector includes a metal material that can conduct electrons. Preferably, the positive electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.
[0125] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the content of the additive is 0.01% to 10%.
[0126] In some embodiments, the additive further comprises at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, and a nitrile compound.
[0127] In some embodiments, the cyclic sulfate ester compound includes at least one of propylene sulfate and methyl vinyl sulfate.
[0128] In some embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, and 1,3-propene sultone.
[0129] In some embodiments, the cyclic carbonate compound includes at least one of vinyl ethylene carbonate, methylene carbonate, fluoroethylene carbonate, or a compound shown in Structural Formula 1:
[0130]
[0131] In the structural formula 1, R 21 , R 22 , R 23 , R 24 , R 25 , R 26Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group.
[0132] In some embodiments, the phosphate compound includes at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate or the compound shown in formula 2:
[0133]
[0134] In the structural formula 2, R 31 , R 32 , R 33 are each independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group.
[0135] In a preferred embodiment, the phosphate compound shown in the structural formula 2 may be at least one of tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate.
[0136] In some embodiments, the nitrile compound includes at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, and sebacononitrile.
[0137] In other embodiments, the additives may also include other additives that can improve battery performance: for example, additives that enhance battery safety performance, such as flame retardant additives such as fluorophosphates and cyclophosphazenes, or overcharge prevention additives such as tert-amylbenzene and tert-butylbenzene.
[0138] It should be noted that, unless otherwise specified, in general, the content of any one of the optional substances in the additives in the non-aqueous electrolyte is less than 10%, preferably, the content is 0.01-5%, and more preferably, the content is 0.1%~2%. Specifically, the content of any one of the optional substances in the additives can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10%.
[0139] In some embodiments, the additive includes fluoroethylene carbonate, and based on the total mass of the non-aqueous electrolyte being 100%, the added amount of the fluoroethylene carbonate is 0.01% to 30%.
[0140] In some embodiments, the lithium salt includes LiPF6, LiTFSI, LiBOB, LiDFOB, LiDFOP, LiBF4, LiSbF6, LiAsF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiClO4, LiAlCl4, LiCF3SO3, LiSO3F, Li2B 10 Cl 10 , lithium chloroborane, lithium tetrafluorooxalate phosphate, lithium trioxalate phosphate, a lower aliphatic lithium carboxylate having 4 or less carbon atoms, or at least one of lithium tetraphenylborate.
[0141] In some embodiments, the concentration of the lithium salt in the non-aqueous electrolyte is 0.1 mol / L to 4 mol / L. In a preferred embodiment, the concentration of the lithium salt in the non-aqueous electrolyte is 0.5 mol / L to 2.5 mol / L. Specifically, in the non-aqueous electrolyte, the concentration of the lithium salt can be 0.5mol / L, 0.55mol / L, 0.6mol / L, 0.65mol / L, 0.7mol / L, 0.8mol / L, 0.85mol / L, 0.9mol / L, 0.95mol / L, 1.0mol / L, 1.1mol / L, 1.15mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.45mol / L, 1.5mol / L, 1.6mol / L, 1.7mol / L, 1.8mol / L, 1.9mol / L, 2.0mol / L, 2.1mol / L, 2.2mol / L, 2.3mol / L, 2.4mol / L or 2.5mol / L. In some embodiments, the battery further includes a diaphragm, which is located between the positive electrode and the negative electrode.
[0142] The diaphragm may be an existing conventional diaphragm, such as a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.
[0143] The present invention is further described below by way of examples.
[0144] Table 1
[0145]
[0146] Note: VC-vinylene carbonate; DTD-vinyl sulfate; LiPO2F2-lithium difluorophosphate; EC-ethylene carbonate; EMC-ethyl methyl carbonate; EP-ethyl propionate.
[0147] Example 1
[0148] This embodiment is used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and includes the following steps:
[0149] The positive electrode preparation steps are as follows: ternary positive electrode active material NCM622, conductive carbon black and binder polyvinylidene fluoride are mixed in a mass ratio of 95:3.0:2.0, dispersed in N-methyl-2-pyrrolidone to obtain positive electrode slurry, the positive electrode slurry is evenly coated on both sides of aluminum foil, and after drying, rolling and vacuum drying, an aluminum lead wire is welded with an ultrasonic welder to obtain a positive electrode plate, the thickness of the plate is between 90-120 μm, and the compaction density of the negative electrode material is controlled to be 3.45 g / cm by the surface density and rolling thickness of the positive electrode material. 3 ;
[0150] The negative electrode preparation steps are as follows: artificial / natural mixed graphite (D50 is 12.7 μm, D90 is 22.4 μm, D50 / D90=0.56), conductive carbon black, binder styrene butadiene rubber and carboxymethyl cellulose are mixed in a mass ratio of 94.7:1.5:2.4:1.4, dispersed in deionized water to obtain a negative electrode slurry, the negative electrode slurry is coated on both sides of the copper foil, and after drying, rolling and vacuum drying, a nickel lead wire is welded with an ultrasonic welder to obtain a negative electrode plate, the thickness of the plate is between 110-130 μm, and the compaction density of the negative electrode material is controlled to be 1.55 g / cm by the surface density and rolling thickness of the negative electrode material. 3 ;
[0151] The electrolyte preparation steps are: ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed at a mass ratio of EC:EMC = 30:70, and LiPF6 and various additives are added after mixing. The LiPF6 concentration in the non-aqueous electrolyte is 1 mol / L, and the content of each additive is shown in Table 1.
[0152] The membrane preparation steps are as follows: using a three-layer isolation membrane of polypropylene, polyethylene and polypropylene with a thickness of 20 μm;
[0153] The battery assembly steps are as follows: placing a three-layer isolation film with a thickness of 20 μm between the positive plate and the negative plate, then winding the sandwich structure consisting of the positive plate, the negative plate and the separator, flattening the wound body and placing it in an aluminum-plastic shell, welding the pole ears and sealing the aluminum-plastic shell to obtain a battery cell to be injected with liquid; cutting and injecting the electrolyte prepared above into the battery cell, sealing it after standing for 1 hour, and aging the sealed battery at 45°C for 48 hours.
[0154] Then, the conventional formation of the first charge was carried out according to the following steps: 0.05C constant current charging for 3 h, 0.1C constant current charging for 2 h, 0.2C constant current charging for 2 h, standing for 1 hr, aging at 45°C for 48 h, and then further charged to 4.4 V at 0.2C constant current, and discharged to 3.0 V at 0.2C constant current.
[0155] Embodiments 2 to 24
[0156] Examples 2 to 24 are used to illustrate the preparation method of the lithium ion battery disclosed in the present invention, and include most of the operation steps in Example 1, except that:
[0157] The particle sizes D50 and D90 of the negative electrode active material, the composition of the non-aqueous organic solvent, the additives and their addition amounts are shown in Table 1.
[0158] Comparative Examples 1 to 13
[0159] Comparative Examples 1 to 13 are used to compare and illustrate the method for preparing a lithium ion battery disclosed in the present invention, and include most of the operating steps in Example 1, except that:
[0160] The particle size D50, D90, non-aqueous organic solvent composition, additives and their addition amounts of the negative electrode material are shown in Table 1.
[0161] Performance Testing
[0162] The lithium ion batteries prepared in the examples and comparative examples were subjected to the following performance tests:
[0163] 1. Low temperature cycle performance test: At -10℃, charge the formed battery to 4.4V with 0.33C constant current and constant voltage, and then discharge it to 3.0V with 0.5C constant current. After 500 cycles of charge / discharge, calculate the capacity retention rate and internal resistance growth rate of the 500th cycle. The calculation formula is as follows:
[0164] The 500th cycle capacity retention rate (%) = (500th cycle discharge capacity / 1st cycle discharge capacity) × 100%;
[0165] Internal resistance growth rate after the 500th cycle (%) = (internal resistance after the 500th cycle - initial internal resistance before the cycle) / initial internal resistance before the cycle × 100%;
[0166] 2. High temperature storage performance: Charge the formed battery to 4.4V at room temperature with 0.5C constant current and constant voltage, then discharge it to 3.0V with 1C constant current, record the initial discharge capacity, then charge it to 4.4V with 0.5C constant current and constant voltage, use the drainage method to test the initial volume of the battery, then store it at 60℃ for 30 days, and after the battery cools to room temperature, discharge it to 3.0V with 1C to measure the battery's retention capacity, and test the battery's volume after storage. The calculation formula is as follows:
[0167] Battery capacity retention rate (%) = retention capacity / initial capacity × 100%;
[0168] Battery storage volume expansion (%) = (volume after storage - initial volume) / initial volume × 100%;
[0169] (1) The test results obtained in Examples 1 to 15 and Comparative Examples 1 to 13 are entered in Table 2.
[0170] Table 2
[0171]
[0172] It can be seen from the test results of Examples 1 to 15 and Comparative Examples 1 to 13 that vinylene carbonate, lithium difluorophosphate and vinyl sulfate are added as additives to the non-aqueous electrolyte, and at the same time, by controlling the D50 / D90 ratio D of the negative electrode material, the mass content ratio X of vinylene carbonate to lithium difluorophosphate and the total mass fraction A of vinylene carbonate, vinyl sulfate and lithium difluorophosphate to satisfy the conditions of 0.15≤D×A / X≤8, and 0.25≤D≤0.9, 0.1≤X≤2.5, 0.3≤A≤2, the obtained lithium ion battery has excellent storage performance at high temperature, and has a higher capacity retention rate and lower impedance at low temperature, and can better balance the electrochemical performance at high and low temperatures. It is speculated that vinylene carbonate, lithium difluorophosphate and vinyl sulfate are decomposed on the surface of the negative electrode active material during the battery formation process, and the purpose of regulating the composition of the negative electrode surface interface film is achieved by regulating the relative ratio of vinylene carbonate, vinyl sulfate and lithium difluorophosphate. By controlling the D50 / D90 ratio of the negative electrode material, it is beneficial to form different surface morphologies and particle overlap effects, thereby affecting the uniformity of the film formation of the interface film on the negative electrode surface; when the D50 / D90 ratio D of the negative electrode material, the mass content ratio X of vinyl carbonate and lithium difluorophosphate, and the sum of the mass fractions A of vinyl carbonate, vinyl sulfate and lithium difluorophosphate reach a state of equilibrium, a dense negative electrode interface film with high ion conduction efficiency can be constructed on the surface of the negative electrode active material. This film can effectively protect the negative electrode and non-aqueous electrolyte from damage during high-temperature storage, and is beneficial to the conduction of lithium ions at low temperatures, ultimately achieving a comprehensive improvement in battery performance.
[0173] From the comparison of the test results of Examples 1 to 7 and Examples 8 to 15, it can be seen that when the D50 / D90 ratio D of the negative electrode material, the mass content ratio X of vinylene carbonate to lithium difluorophosphate, and the mass fraction sum A of vinylene carbonate, vinyl sulfate and lithium difluorophosphate further meet the conditions of 0.2≤D×A / X≤7, and 0.3≤D≤0.17, 0.15≤X≤1, 0.6≤A≤1.6, the obtained lithium ion battery has better high temperature storage performance and low temperature cycle performance. At the same time, in Examples 11 to 15, when the content of vinylene carbonate is greater than that of lithium difluorophosphate, or when the content of vinyl sulfate is greater than that of lithium difluorophosphate, the proportion of inorganic phase in the interface film on the surface of the negative electrode decreases, resulting in insufficient structural stability of the interface film on the surface of the negative electrode, which is easy to rupture at high temperature, resulting in the occurrence of non-aqueous electrolyte side reactions in lithium ion batteries under high temperature storage, causing battery gas production.
[0174] From the test results of Comparative Examples 1 to 3, it can be seen that when none of vinylene carbonate, lithium difluorophosphate and vinyl sulfate is added to the non-aqueous electrolyte, the electrochemical performance of the obtained lithium-ion battery at high temperature and low temperature is reduced, indicating that the battery system provided in the present application relies on the combination of vinylene carbonate, lithium difluorophosphate and vinyl sulfate to obtain a negative electrode surface interface film with better performance.
[0175] From the test results of Comparative Examples 4 to 8, it can be seen that when the D value, X value and A value are too high or too low, even if the condition 0.15≤D×A / X≤8 is met, the high and low temperature performance of the lithium ion battery will be deteriorated, indicating that the D50 / D90 ratio D of the negative electrode material, the mass content ratio X of vinyl carbonate to lithium difluorophosphate, and the total mass fraction A of vinyl carbonate, vinyl sulfate and lithium difluorophosphate all have a great influence on the high and low temperature performance of the lithium ion battery.
[0176] From the test results of Comparative Examples 9 to 13, it can be seen that when the D value, the X value and the A value meet the content range limit but do not meet the condition 0.15≤D×A / X≤8, the obtained lithium ion battery also does not have good high and low temperature electrochemical performance, indicating that there is a mutual influence between the D50 / D90 ratio D of the negative electrode material, the mass content ratio X of vinyl carbonate to lithium difluorophosphate, and the total mass fraction A of vinyl carbonate, vinyl sulfate and lithium difluorophosphate. When and only when the three reach a good equilibrium state, the high temperature stability and ion conduction efficiency of the negative electrode interface film can be significantly improved.
[0177] (2) The test results obtained in Examples 1 and 16 to 21 are entered in Table 3.
[0178] Table 3
[0179]
[0180] From the comparison of the test results of Examples 1 and 16 to 21, it can be seen that compared with Examples 20 and 21, when the mass content ratio of ethylene carbonate to ethyl methyl carbonate in the non-aqueous organic solvent in Examples 1 and 16 to 19 is in the range of 0.15 to 0.6, the lithium deposition / stripping polarization voltage can be reduced and the cycle life in a wide temperature range can be extended.
[0181] (3) The test results obtained in Examples 1 to 3 and Examples 22 to 24 are entered in Table 4.
[0182] Table 4
[0183]
[0184] From the comparison of the test results of Examples 1 to 3 and Examples 22 to 21, it can be seen that in the battery system provided by the present invention, after adding carboxylate ethyl propionate (EP) as a non-aqueous organic solvent, although the low-temperature capacity retention rate and low-temperature impedance growth rate of the lithium-ion battery are improved to a certain extent, the high-temperature storage performance of the lithium-ion battery is significantly deteriorated, making it difficult for the lithium-ion battery to better balance high and low temperature performance.
[0185] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: It comprises a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the negative electrode comprises a negative electrode material layer containing a negative electrode material, the non-aqueous electrolyte comprises a non-aqueous organic solvent, a lithium salt and an additive, the additive comprises vinylene carbonate, lithium difluorophosphate and vinyl sulfate, the mass percentage of lithium difluorophosphate is greater than the mass percentage of vinyl sulfate; the non-aqueous organic solvent comprises vinyl carbonate and ethyl methyl carbonate, the mass content ratio of vinyl carbonate to ethyl methyl carbonate in the non-aqueous organic solvent is 0.15-0.6, and the mass percentage of ethyl methyl carbonate in the non-aqueous organic solvent is greater than or equal to 20%; the mass percentage of vinylene carbonate in the non-aqueous electrolyte is 0.1%-0.35%; the mass percentage of lithium difluorophosphate in the non-aqueous electrolyte is 0.3%-0.75%; the mass percentage of vinyl sulfate in the non-aqueous electrolyte is 0.05%-0.75%; The lithium-ion battery meets the following conditions: 0.08≤D*A / X≤8, and 0.25≤D≤0.9, 0.1≤X≤2.5, 0.3≤A≤2; Where D is the D50 / D90 ratio of the negative electrode material; X is the mass content ratio of vinylene carbonate to lithium difluorophosphate in the non-aqueous electrolyte; A is the sum of the mass fractions of vinylene carbonate, vinyl sulfate and lithium difluorophosphate in the non-aqueous electrolyte, expressed in wt%.
2. The lithium-ion battery according to claim 1, characterized in that The lithium-ion battery meets the following conditions: 0.2≤D*A / X≤7.
3. The lithium-ion battery according to claim 1, characterized in that The D50 / D90 ratio D of the negative electrode material is 0.3-0.75; and / or The D50 of the negative electrode material is 9-20 μm.
4. The lithium-ion battery according to claim 1, characterized in that The mass content ratio X of vinylene carbonate to lithium difluorophosphate in the non-aqueous electrolyte is 0.15-1.
5. The lithium-ion battery according to claim 1, characterized in that: The non-aqueous organic solvent does not contain carboxylic acid ester.
6. The lithium-ion battery according to claim 1, characterized in that The negative electrode active material includes one or more of artificial graphite and natural graphite.
Citation Information
Patent Citations
Electrolyte of high-nickel ternary system capacitor battery and preparation method thereof
CN109887764A
Lithium ion battery electrolyte and lithium ion battery
CN110265716A
Lithium ion battery electrolytic solution and lithium ion battery
CN111653829A
Secondary battery and electric device
CN117613356A